2016
DOI: 10.3748/wjg.v22.i19.4695
|View full text |Cite
|
Sign up to set email alerts
|

Qinggan Huoxue Recipe suppresses epithelial-to-mesenchymal transition in alcoholic liver fibrosis through TGF-β1/Smad signaling pathway

Abstract: Qinggan Huoxue Recipe inhibits EMT in ALF rats by modulating the TGF-β1/Smad signaling pathway, suggesting that the mechanism underlying the amelioration of ALF induced by QGHXR is associated with this pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In our study, the compound treatment significantly decreased relative mRNA and/or protein expression levels of hepatic TGF- β 1, (phospho-)Smad2, and (phospho-)Smad3 but increased the Smad7 expression. The changes of TGF- β 1 and Smads are consistent with previous studies about the molecular mechanism of liver fibrosis [3941], suggesting that the protective effect of the compound is via TGF- β 1/Smad signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the compound treatment significantly decreased relative mRNA and/or protein expression levels of hepatic TGF- β 1, (phospho-)Smad2, and (phospho-)Smad3 but increased the Smad7 expression. The changes of TGF- β 1 and Smads are consistent with previous studies about the molecular mechanism of liver fibrosis [3941], suggesting that the protective effect of the compound is via TGF- β 1/Smad signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…In schistosome-induced liver damage, abnormal SOD expression was found to promote liver fibrosis [ 31 , 32 ]. In a previous study, it was shown that serum HA levels were significantly increased in rat liver fibrosis [ 33 , 34 ]. In the present study, we showed that S. japonicum infection induced serum HA levels and reduced SOD activities in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Any chronic form of hepatic injury can result in the transformation of hepatocytes into mesenchymal cells by an epithelial–mesenchymal transition (EMT) process. EMT is a dynamic program in which fully differentiated epithelial cells undergo a phenotypic change, resulting in loss of marker proteins such as E-cadherin and zonula occludens-1 (ZO-1), and acquisition of mesenchymal characteristics such as α-SMA, vimentin, matrix metalloproteinase (MMP)-2, MMP-9, and collagens [ 7 , 8 ]. In addition, following damage to the epithelial cells, bile-duct epithelium and hepatocytes released the profibrogenic cytokine that further activates HSCs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified that a variety of cytokines and growth factors, including transforming growth factor-β1 (TGF-β1), epidermal growth factor (EGF), and hepatocyte growth factor (HGF), participate in the EMT process [ 7 , 15 , 16 ]. TGF-β1/Smad signaling has been reported as a mechanism leading to hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%